Serum Homocysteine Level and Ankle-Brachial Index in Peripheral Arterial Disease (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2020)
Patients with peripheral arterial disease have a higher risk of death compared to normal populations. There are several relatively new risk factors significantly increase the vulnerability to suffering from peripheral arterial disease, one of which is homocysteine. Studies investigating the role of serum homocysteine level as a biomarker of the severity of peripheral arterial disease based on an ankle-brachial index (ABI) in the different populations were still limited and it was never been studied in Mataram. This was a cross-sectional study aimed to investigate the correlation between serum homocysteine level and ABI in 77 peripheral artery disease (PAD) outpatients in Siti Hajar Hospital, Mataram. The diagnosis of PAD was based on ABI0.9. Fasting serum homocysteine level was examined using the ELISA technique. Characteristic data collected were gender, age, hypertension, diabetes mellitus, and body mass index (BMI) category. There was a significant correlation between the increase of serum homocysteine levels and the decrease of ABI. The main risk factors for peripheral arterial disease in the subjects are hypertension, diabetes mellitus, and overweight/obesity. Serum homocysteine level is a predictor of peripheral arterial disease severity measured using ABI.